Pengaruh Komponen Risk Based Bank Rating Terhadap Harga Saham pada Perusahaan Perbankan BUMN - Mayang Murni; Lily Karlina Nasution; Ika Sari Dewi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
ABSTRACT A good financial services company can be reflected in the quality of its issuer's performance. In banking companies, there are several indicators for assessing bank health, one of which is the Risk Based Bank Rating. This assessment component is used to observe its effect on share prices. This research aims to observe the influence of the risk profile through Net Performing Loan, good corporate governance through institutional ownership, managerial ownership, the audit committee, the board of commissioners, earnings through ROA, capital through CAR, and efficiency using BOPO on share prices of state-owned banking companies in Indonesia from 2017–2021. The data used is secondary data from the financial reports of state-owned banking companies in Indonesia and was analyzed using multiple linear regressions. The results showed that simultaneously, the variables institutional ownership, managerial ownership, audit committee, board of commissioners, ROA, CAR, NPL, and BOPO have a significant effect on share prices. Meanwhile, only the institutional ownership, managerial ownership, and ROA variables have a positive and significant effect on share prices.